Aplikasi Sistem Penjualan Kompresor Dengan After Sales Service Berbasis Web Pada PT XYZ (Riwayat: Educational Journal of History and Humanities, 2026)
Digital transformation in engineering companies requires sales and after-sales activities to be managed in an integrated and well-documented manner. PT XYZ, an official distributor of ABC Indonesia, still performs many processes manually, starting from recording orders, scheduling technicians, and monitoring project progress to handling warranty claims. These conditions create a risk of miscommunication between divisions, delays in completing work, and difficulties in tracing project and service history. This study aims to design and develop a web-based compressor sales application with after-sales service that fits the operational needs of the company.The system was developed using the SDLC Waterfall model through the stages of requirements analysis, design, implementation, and testing. Business and system processes were modelled using BPMN and UML, while the application was implemented with the Laravel framework and a MySQL database. The system provides several main modules, including master data management, sales order management, engineer and technician scheduling and assignment, project progress monitoring, work report management, warranty claim handling, order and project history, and notifications for each user role (Admin, Sales, Engineer, and Technician). Through the integration of these modules, sales and project workflows are recorded in a single centralized platform.System testing was carried out using alpha testing based on usage scenarios of each module for each role. The results show that all main functions run according to the expected outcomes, both in managing orders, scheduling, monitoring projects, and processing warranty claims. The resulting application helps the company reduce its dependence on manual procedures, improve traceability of work history, and support coordination between divisions in managing projects and after-sales services in a more efficient and structured manner.